2015
DOI: 10.1007/s11284-015-1268-0
|View full text |Cite
|
Sign up to set email alerts
|

Total volume of 3D small patch reefs reflected in aerial photographs can predict total species richness of coral reef damselfish assemblages on a shallow back reef

Abstract: Because fish have a high dispersal ability, an understanding coral reef fish metacommunity structure is vital for effective conservation. Coral reefs provide patchy habitat of various sizes and scales. We examined the species-area relationship (SAR) of damselfish (Pomacentridae) assemblages over 81 environmentally homogenous patch reefs ranging 0.07-45.4 m 2 with low coral cover. Patch reefs were located in the shallow back reef (<2.5 m deep) off Ishigaki Island, Japan. Reef area was measured by performing ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Although number of anemones was found to show a stronger correlation with the product of total area and total perimeter of dark-colored patch reefs than with total area alone (Hattori and Kobayashi 2007), the perimeter of dark-colored patch reefs could not be determined in this study (see ''Materials and methods''). After measuring height of 84 patch reefs within the present study site (2.9 ha), Hattori and Shibuno (2015) suggested that total volume ( P reef basement area · reef height) of dark-colored patch reefs is an indicator of total species richness of damselfish assemblages within shallow back reefs. Accordingly, we expected that total area of tall patch reefs (>1.5 m in height) that were detected on a sequence of two aerial images with a stereoscope would indicate anemonefish abundance.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although number of anemones was found to show a stronger correlation with the product of total area and total perimeter of dark-colored patch reefs than with total area alone (Hattori and Kobayashi 2007), the perimeter of dark-colored patch reefs could not be determined in this study (see ''Materials and methods''). After measuring height of 84 patch reefs within the present study site (2.9 ha), Hattori and Shibuno (2015) suggested that total volume ( P reef basement area · reef height) of dark-colored patch reefs is an indicator of total species richness of damselfish assemblages within shallow back reefs. Accordingly, we expected that total area of tall patch reefs (>1.5 m in height) that were detected on a sequence of two aerial images with a stereoscope would indicate anemonefish abundance.…”
Section: Discussionmentioning
confidence: 86%
“…Why could total area of dark-colored patch reefs reflect fish abundance in the present study? Volume of patch reef (i.e., reef area · reef height) was reported better explained by a linear than a power approximation of reef area in a shallow back reef site, although that study assessed only 84 patch reefs (Hattori and Shibuno 2015). Presuming that a small patch reef is a hemisphere of radius r, the living space around this reef is proportional to reef volume (Figs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the contrary, morphometric characteristics such as rugosity and colony shape volume and surface area could be better quantified by suitably accurate 3D surveys at appropriate spatial scales (Reichert et al 2016). Moreover, 3D metrics could provide useful information on the ability of a diversity of organisms to use corals as shelter as well as the influence of reef structure on local hydrodynamics and the amount of light received by the coral colony (Collin et al 2018;Palma et al 2017;Lenihan et al 2015;Hattori and Shibuno 2015). To date, difficulties in collecting 3D data at even modest spatial scales of 1 to 10s of meters has limited the usefulness of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, coral reef protection has become a priority in many governmental agendas (e.g., [12]). This has resulted in the development and implementation of scientific surveys and monitoring programs aimed at evaluating the causes, effects and extent of coral threats (e.g., sedimentation, bleaching and climate change) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%